The Comparison Between The Novel And The Movie Of The Count Of Monte Cristo: A Structural Analysis - Widawati, Ary (2004)
This study deals with the similarities and the differences of the structural elements of the novel and the film of The Count of Monte Cristo. She sets two objectives: the first is to analyze the similarities and differences, and the second is to find out the similarities and differences of the structural elements of the film and the novel. This study is a qualitative study. The data forms are texts and pictures. They are taken from the film and the novel of The Count of Monte Cristo as the object of the study. There are two kinds of data sources: primary and secondary. The primary data sources are the novel and the script of TCMC, while the secondary data sources are any articles and books related to the subject. In conducting her research, the writer uses two methods. The first is descriptive qualitative method. It is used to describe the structural elements. The second is the comparative method. The comparative method is used to compare the structural analysis of the film and the novel of The Count of Monte Cristo. The outcomes of the study are as follows: first, basically there are similarities and differences of the structural elements of the two works. The basic similarity of them is the same theme. The second conclusion is that the decision to make the adapted version different to the original version is based on the budget and commercial reason